Mediasi Sebagai Instrumen Penyelesaian Sengketa Bisnis: antara Kepastian Hukum dan Efisiensi Waktu - Igusti Lanang Bagus Priangga Krisna (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Dispute resolution in the business world is inevitable, particularly in the modern era marked by the complexity of commercial relationships. Mediation, as one form of alternative dispute resolution (ADR), offers a faster and more efficient solution compared to litigation. This article aims to examine the legal status of mediation within the business dispute resolution system in Indonesia, assess the extent to which mediation can provide legal certainty for disputing parties, and analyze its effectiveness in achieving time efficiency. The method used is a normative juridical approach, with analysis of relevant laws and court decisions. The study finds that mediation has a strong legal basis within the national legal system, yet in practice still faces implementation challenges that affect legal certainty. Nevertheless, mediation proves to be more time-efficient than formal litigation. Therefore, strengthening regulations and improving the competence of mediators are key factors in optimizing mediation as an instrument for resolving business disputes in Indonesia.